التطور العمراني لحي السيدة زينب بين القيود البيئية والمعالم التراثية - وردة أحمد السيد محمد (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd)
يتناول هذا البحث دراسة التطور العمراني لحي السيدة زينب في ضوء ما يواجهه من قيود بيئية وما يزخر به من معالم تراثية ،  وقد ارتكزت الدراسة على تحليل نشأة الحي وتطوره فوق المسرح الطبيعي للأرض، مع التركيز على دور المجاري المائية القديمة مثل الخليج المصري، والخليج الناصري، وعدد من البرك التاريخية، وتأثيرها في توجيه العمران. كما سلطت الدراسة الضوء على اتجاهات التوسع العمراني الأفقي في القاهرة، خاصة نحو الشمال والغرب، وأثر ذلك على حي السيدة زينب، وتطوّر نسيجه العمراني. وتناولت أيضًا خريطة المناطق الأثرية ضمن المركّب العمراني ذي الاستخدامات غير السكنية، إضافة إلى تحليل البيئة العمرانية للحي من حيث أنماط استخدام المباني، وخصائصها المعمارية، وشبكة الطرق، وجودة البيئة المكانية. واختُتمت الدراسة برصد أبرز المشكلات الحضرية المرتبطة بالتطور، واقتراح استراتيجية للإرتقاء بالحي، من خلال تحليل مظاهر التحوّل، وتحديد فرص التنمية، والتأكيد على أهمية إعادة الإستخدام التكيّفي للمباني التاريخية، وقد خلصت الدراسة إلى مجموعة من النتائج والتوصيات الداعمة لحماية هوية الحي وتعزيز تنميته المستدامة. This research examines the urban development of the Sayyida Zeinab district in light of the environmental constraints it faces and the rich heritage sites it contains. The study focuses on analyzing the origins and development of the district on the natural terrain, focusing on the role of ancient waterways such as the Egyptian Gulf, the Nasser Gulf, and a number of historical ponds, and their impact on urban planning. The study also sheds light on trends in horizontal urban expansion in Cairo, particularly to the north and west, and its impact on the Sayyida Zeinab neighborhood and the development of its urban fabric. It also covers a map of archaeological sites within the urban complex with non-residential uses, in addition to analyzing the neighborhood's urban environment in terms of building usage patterns, architectural characteristics, road network, and spatial environmental quality. The study concluded by identifying the most prominent urban problems associated with development, and proposing a strategy for upgrading the neighborhood by analyzing the manifestations of transformation, identifying development opportunities, and emphasizing the importance of adaptive reuse of historic buildings. The study concluded with a set of findings and recommendations that support the protection of the neighborhood's identity and the promotion of its sustainable development.